Ecological niches in the polyploid complex Linum suffruticosum s.l. - Afonso, Ana; Castro, Sílvia; Loureiro, João; Arroyo, Juan; Figueiredo, Albano; Lopes, Sara; Castro, Mariana (Frontiers in Plant Science, 2023)
The high frequency of polyploidy in the evolutionary history of many plant groups occurring in the Mediterranean region is likely a consequence of its dynamic paleogeographic and climatic history. Polyploids frequently have distinct characteristics that allow them to overcome the minority cytotype exclusion. Such traits may enable polyploid individuals to grow in habitats different from their parentals and/or expand to new areas, leading to spatial segregation. Therefore, the successful establishment of polyploid lineages has long been associated with niche divergence or niche partitioning and the ability of polyploids to cope with different, often more stressful, conditions. In this study, we aimed to explore the role of environmental variables associated with the current distribution patterns of cytotypes within the polyploid complex Linum suffruticosum s.l.. The distribution and environmental niches of the five main cytotypes of L. suffruticosum s.l. (diploids, tetraploids, hexaploids, octoploids and decaploids) were studied across its distribution range. Realized environmental niche of each cytotype was determined using niche modelling tools, such as maximum entropy modelling and niche equivalency and similarity tests. Differences in the environmental conditions of L. suffruticosum s.l. cytotypes were observed, with polyploids being associated with habitats of increased drought and soil pH, narrower temperature ranges and decreased soil water and cation exchange capacities. Diploids present the widest environmental niche, and polyploids occupy part of the diploid niche. Although some polyploids have equivalent potential ecological niches, cytotypes do not co-occur in nature. Additionally, the ecological niche of this polyploid complex is different between continents, with North African habitats being characterised by differences in soil texture, higher pH, and low cation exchange capacity, precipitation and soil water capacity and higher temperatures than habitats in southwest Europe. The different ecological conditions played a role in the distribution of cytotypes, but the mosaic distribution could not be entirely explained by the environmental variables included in this study. Other factors, such as reproductive isolation and competitive interactions among cytotypes, could further explain the current diversity and distribution patterns in white flax. This study provides relevant data on the niche requirements of each cytotype for further competition and reciprocal transplant experiments.